Analisis Penggunaan Sorekara, Soshite, dan Soreni dalam Website Surat Kabar Asahi.Com - Rudi Hartono Manurung (Bina Nusantara University, 2013)
Setsuzokujoshi is a particle that shows the relationship between sentences, as well as having an important role in sentences. What characterizes setsuzokujoshi is its position which is always located between two sentences. Setsuzokujoshi, which is part of particles in Japanese, has many types. In this study, the researcher will limit the research on the use of それから, そして, それに contained in the newspaper articles of asahi.com website. The research method used is descriptive and library methods. This study intends to determine the function of setsuzokujoshi それ から, そして, それに and whether it can replace each other in a sentence and that Japanese language learners can determine the apparent similarities and differences between sorekara, soshite, and soreni, so that Japanese language learners can use them correctly. After analyzing the data, it is found that some conclusions namelyそして is used to strengthen problems of a topic of conversation because there is awareness of the speaker. It is often used when combining a topic of conversation. While それ から is reinforcing actions in sequence-based. That is, there will be a second activity to be performed or occurring after the first activity is completed. それに has a function to add anything else to a case. Because それ から has functions similar to そして, there is a possibility for そしてto be replaced by それ から or vice versa.